How to Talk to Data Scientists : A Guide for Executives. - Elser, Jeremy (New York : Business Expert Press, 2021)
This book provides business executives with a concrete exercise, populating a "Master Table," accessible to nontechnical managers and data scientists, which serves as the connective tissue between them. Rather than teach a diluted version of data science, this book describes how to start projects and how to detect and fix problems--the moments when leadership is critical. Insights are provided through real world examples, including a Playbook featuring common projects. The intended audience is executives (C-suite through VP). However, ambitious mid-level managers and data scientists will also benefit.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Chapter 1: Introduction -- Chapter 2: What Is Data Science -- Chapter 3: The Master Table -- Chapter 4: Mistakes Machines Make -- Chapter 5: Mistakes Business Analysts Make -- Chapter 6: Mistakes Data Scientists Make -- Chapter 7: How to Properly Deploy Data Science -- Chapter 8: Playbook -- References -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Big data; Business communication; Data mining; Electronic books